A review on the current status of various hydrothermal technologies on biomass feedstock. (January 2018) - Kumar, Mayank; Olajire Oyedun, Adetoyese; Kumar, Amit
Abstract: Hydrothermal processing, a thermochemical approach, is an excellent method of converting energy-rich biomass into useful products. This approach offers the advantage of handling biomass with relatively high moisture content by precluding an energy-intensive pretreatment step. Hydrothermal processing is of world-wide interest in view of depleting fossil-fuel reserves and increased environmental greenhouse gas emissions. There is potential to develop this novel technology at demonstration scale. This paper reviews the three hydrothermal technologies, namely hydrothermal liquefaction, gasification and carbonization, to provide insight into the likelihood of commercialization. The study discusses the role of different process parameters that have key impacts on the quality and yield of the desired products. This study also identifies the gaps in the literature including the need to establish a baseline to develop key process models and to perform a techno-economic assessment to get a better sense of the viability of the technology in future.